Trade and Development report 1989 : report by the secretariat of the United Nations Conference on Trade and Development - United Nations; United Nations Conference on Trade and Development, Geneva (New York : United Nations, 1989)
This report discusses mainly the international economic environment in 1988, the prospects for 1989-1990. Some of which are aspects of financing and payments in the trade of developing countries, and the trade policies and the new trade legislation of the developed market-economy countries.
Includes bibliographical references: p. 207-209.
ne 16/04/2019
Ref
Keywords: Commerce; Economic development; Economic history; Developing countries